Sentiment analysis on the web - Chit, Lin Su. (2013)
In the Information Age, the wide range of Web usage has been increasing due to the advancement in hardware and software technology. As a result of that, the Web becomes the valuable source of massive amount of data contents. Nowadays, large volumes of data are created by Internet users. Among the different kinds of data available on the Web, considerable amount of data comes from social media. This is the place where users express themselves freely in the context of various topics. Therefore, sentiment data has gained increasing attention from both business and consumer to discovery valuable knowledge from these kinds of data. However, in order to accomplish analyzing the sentiment data, step by step processes have to be executed.